2005
DOI: 10.1097/01.brs.0000155407.87439.a2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Shortening on the Spinal Cord: An Experimental Study

Abstract: Acute spinal column shortening can be characterized into 3 phases. Phase 1, safe range: occurred during shortening within one-third of the vertebral segment and is characterized by no deformity of the dural sac or the spinal cord. Phase 2, warning range: occurred during spinal shortening between one-third and two-thirds of the vertebral segment and is characterized by shrinking and buckling of the dural sac and no deformity of the spinal cord. Phase 3, dangerous range: occurred after shortening in excess of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 40 publications
2
91
0
2
Order By: Relevance
“…Meanwhile, excessive displacement and overlapping of the dural sac could be observed and prompt adjustment could be performed during the whole procedure. The clinical observation and animal experiences by Kawahara et al [13] also confirmed that the spine shortened within one-third of the height of the vertebral would not lead to the functional change of the spinal cord. In our opinion, an observed wrinkle or kink of the dura sac no greater than 2-3 cm was admissible and would not lead to positive neurological impact.…”
Section: Discussionmentioning
confidence: 48%
“…Meanwhile, excessive displacement and overlapping of the dural sac could be observed and prompt adjustment could be performed during the whole procedure. The clinical observation and animal experiences by Kawahara et al [13] also confirmed that the spine shortened within one-third of the height of the vertebral would not lead to the functional change of the spinal cord. In our opinion, an observed wrinkle or kink of the dura sac no greater than 2-3 cm was admissible and would not lead to positive neurological impact.…”
Section: Discussionmentioning
confidence: 48%
“…A PSO can apply to patients with sharp, angular kyphosis and anterior column fusion [3]. Nevertheless, the excessive shortening of the area variable for the cord can be dangerous with a PSO and authors have recommended limiting the correction to 30-40° [7]. Therefore, neither the SPO nor a PSO would be suitable to correct a severe kyphotic deformity with a Konstam's angle beyond 90°.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most authors hold that one-stage neural decompression, such as enlargement of the foramen magnum, drainage of syringomyelia and resection of filum terminale, is necessary. But recent studies [20][21][22][23][24] have demonstrated that shortening of the spine can improve the morphology and tension of the spinal cord, thus improving its function. Xie et al [25] believed that, for adolescents with a main curve [90°or associated with significant neurologic deficits before surgery, PVCR was appropriate and effective alternative because it could appropriate shortening of the spinal cord improves the blood supply, decrease the tension of spinal cord and, subsequently, the function of the spinal cord.…”
Section: Clinical Factorsmentioning
confidence: 99%